The Use of Virtual Characters to Assess and Train Non-Verbal Communication in High-Functioning Autism - Georgescu, Alexandra Livia; Kuzmanovic, Bojana; Roth, Daniel; Bente, Gary; Vogeley, Kai (Frontiers in Human Neuroscience, 2014)
High-functioning autism (HFA) is a neurodevelopmental disorder, which is characterized by life-long socio-communicative impairments on the one hand, and preserved verbal and general learning and memory abilities on the other. One of the areas where particular difficulties are observable is the understanding of nonverbal communication cues. Thus, investigating the underlying psychological processes and neural mechanisms of nonverbal communication in HFA allows a better understanding of this disorder, and potentially enables the development of more efficient forms of psychotherapy and trainings. However, the research on nonverbal information processing in HFA faces several methodological challenges. The use of virtual characters helps to overcome such challenges by enabling an ecologically valid experience of social presence, and by providing an experimental platform that can be systematically and fully controlled. To make this field of research accessible to a broader audience, we elaborate in the first part of the review on the validity of using virtual characters in nonverbal behavior research on HFA, and we review current relevant paradigms and findings from social cognitive neuroscience. In the second part we argue for the use of virtual characters as either agents or avatars in the context of “transformed social interactions”. This allows for the implementation of real-time social interaction in virtual experimental settings, which represents a more sensitive measure of socio-communicative impairments in HFA. Finally, we argue that virtual characters and environments are a valuable assistive, educational and therapeutic tool for HFA.